Dynamic Response and Settlement Cause Analysis of Roadbed–Soft Clay Foundation System Under Traffic Vibration Loads - Fan Xia; Tangdai Xia; Zihao Wang (Applied Sciences)
Roadbeds constructed on soft clay foundations often experience substantial post-construction settlement under long-term traffic loading. To investigate this phenomenon, numerical simulations were conducted to study the vibration response of various roadbed–foundation systems subjected to pavement vibration loads, and the propagation patterns of vibration waves within these systems were analyzed. Vibration reconsolidation tests were performed to examine the reconsolidation behavior of soft clays under vibration loads (cyclic loads without overall compressive or tensile tendencies) following initial consolidation under static loads. The influence of vibration load frequency and amplitude on the reconsolidation effect was briefly analyzed. By combining the analysis of the consolidation mechanism of soft clays under vibration loads, this study investigated the reasons for the large post-construction settlement of roadbed–soft clay foundation systems under traffic vibration loads from both wave propagation and vibration perspectives. Based on the focus on the equilibrium state reached by the soil under vibration loads, the vibration reconsolidation test represents a new research approach. In addition to deepening the understanding of the post-construction settlement phenomenon of foundations under traffic loads, it can also provide guidance for practical engineering applications such as foundation treatment and sludge solidification using vibration loads, generating potential economic benefits.